Extraction and characterization of pectin from calamansi peels - Bartolome, Anna Patricia A.
Pectin was extracted from the peels of calamansi. Box-Behnken response surface methodology was used in order to optimize the method. A linear model was generated which showed that solid to liquid ratio(p=0.0001), time(p=0.0376), and temperature(p=0.0032) had significant effects on the pectin yield while pH(p=0.7665) did not. The model was verified witht using the optimal conditions of: temperature- 89.99oC, pH- 1.519, C-120 minutes, and, D- 4.99, yielding 3.48% of pectin. Pectin from the optimized method was characterized based on different physicochemical properties. Based on the results of the physicochemical tests, the calamansi pectin is suitable for commerical use due to its high purity (%AUA=88.35%± 2.70%) and capacity, ability to form aqeous solutions, and ability to form slow setting gels with high soluble solids and good spreading ability (%MeO= 10.09% ± 0.17%; %DE= 60.05% ± 1.42%). However, its low equivalent weight (EW= 445.8 ± 18.03 mg/mmol) and inability to dissolve at low temperatures of water limits the possible applications of the calamansi pectin. The calamansi pectin passed the standards of the US Pharmacopeia for commercial pectin but its low yield makes the commercial extraction uneconomical.